Health screening and its association with emergency department visits and related costs among home-dwelling older adults - Kanninen, Jonna-Carita; Kautiainen, Hannu; Holm, Anu (TAYLOR & FRANCIS LTD, 2025)
Background
The aim of this study was to evaluate the effectiveness of the health screening procedure for home-dwelling older adults in reducing emergency department visits and associated costs.
Methods
Data were derived from health screenings from 2020 to 2021 for 75-year-old home-dwelling residents of Western Finland. The study compared emergency department visits and associated costs between older adults who participated in the health screening (intervention group) and those who did not (non-intervention group). For each older adult, three non-intervention controls were matched according to age, sex, health screening year and wellbeing service county. Emergency department visits and International Classification of Diseases (ICD)-10 codes from one year before to two years after health screening were analyzed.
Results
In the non-intervention group, a 19% increase in emergency visit rates was seen (457-564 per 1000 person-years), while the intervention group showed a 67% decrease (165-23). Annual costs for the non-intervention group increased from 148 euros () to 183, a mean ratio increase of 1.24 per person-year (range 1.08-1.40). In contrast, the intervention group's costs decreased from 53 to 8, a mean reduction ratio of 0.15 per person-year (range 0.10-0.71). The intervention group had lower frequency of visits for respiratory and circulatory diseases but higher for digestive and metabolic diseases, unlike the non-intervention group.
Conclusions
The implementation of the health screening is an effective strategy for reducing both the frequency of emergency department visits and associated costs in home-dwelling older adults in good condition.